The Effect of Compensation and Work Environment On Commitment To The Organisation With Job Satisfaction As An Intervening Variable (Empirical Study at One of the F&B Companies in Bogor City) - Rezeki Agung; Nancy Yusnita; Martinus Tukiran (Dinasti Publisher, 2024)
Organisational commitment is a very important aspect in the world of work, as it has a direct impact on various factors that affect the success of the company. Employees who have high organisational commitment tend to show higher productivity, strong loyalty and better quality of work. In addition, strong organisational commitment reduces employee turnover rates, minimises recruitment and training costs, and helps retain knowledge and expertise within the organisation. Organisational commitment needs to be supported by appropriate compensation, a supportive work environment and employee job satisfaction. With the continuous role between these variables, it is expected to increase commitment to the organisation. This study aims to determine how to increase organisational commitment by identifying the direct and indirect effects of compensation, work environment and job satisfaction on organisational commitment at Raindear Coffee & Kitchen. This type of research method is a quantitative method using survey techniques. The population used in this study were employees of Raindear Coffee & Kitchen. The analysis technique used is descriptive statistics and path analysis with a total research sample of 112 respondents of Raindear Coffee & Kitchen employees. The results of this study found that there is a direct effect of compensation on job satisfaction with a coefficient value of 0.478, there is a direct effect of the work environment on job satisfaction with a coefficient value of 0.394, there is a direct effect of compensation on organisational commitment with a coefficient value of 0.239, there is a direct effect of work environment on organisational commitment with a coefficient value of 0.273, there is a direct effect of job satisfaction on organisational commitment with a coefficient value of 0.321, there is a indirect effect of compensation on organisational commitment through job satisfaction with a coefficient value of 0.153, there is a indirect effect of work environment on organisational commitment through job satisfaction with a coefficient value of 0.126. In order to enhance employee organisational commitment, management should ensure what compensation is in accordance with employee expectations and what work environment can support employees so as to increase productivity, work quality, and employee retention rates.